Pan-genome wide identification and analysis of the SAMS gene family in sunflowers (Helianthus annuus L.) revealed their intraspecies diversity and potential roles in abiotic stress tolerance - Zhang, Chun; Li, Haoyu; Yin, Jiamin; Han, Zhibin; Liu, Xinqi; Chen, Yang (Frontiers in Plant Science, 2024)
S-adenosylmethionine (SAM), a key molecule in plant biology, plays an essential role in stress response and growth regulation. Despite its importance, the SAM synthetase (SAMS) gene family in sunflowers (Helianthus annuus L.) remains poorly understood. This study identified 58 SAMS genes across nine cultivated sunflower species, which were phylogenetically classified into two clades with seven distinct subgroups. Clade I branching into three pairs of group genes (SAMS1 and 5, SAMS6 and 2, as well as SAMS4 and 7) likely resulting from recent WGT-1 and WGD-2 genome duplication events. Collinearity analysis revealed segmental duplications as the primary driver of gene family expansion and all duplicated genes were under purifying selection. The codon usage bias analysis suggested that natural selection substantially shapes the codon usage patterns of sunflower SAMS genes, with a bias for G/C-ending high-frequency codons, particularly encoding glycine, leucine, and arginine. Analysis of the cis-regulatory elements in promoter regions, implied their potential roles in hormones and stress responsiveness. Differential expression patterns for HanSAMS genes were observed in different tissues as well as under hormone treatment or abiotic stress conditions by analyzing RNA-seq data from previous studies and qRT-PCR data in our current study. The majority of genes demonstrated a robust response to BRA and IAA treatments in leaf tissues, with no significant expression change observed in roots, suggesting the response of HanSAMS genes to hormones is tissue-specific. Expression analyses under abiotic stresses demonstrated diverse expression profiles of HanSAMS genes, with HanSAMS5 showing significant upregulation in response to both drought and salt stresses. This comprehensive genomic and expression analysis provides valuable insights into the SAMS gene family in sunflowers, laying a robust foundation for future functional studies and applications in crop improvement for stress resilience.